The Role of Gender in Violence Experienced by Adults With Developmental Disabilities. Issue 1 (January 2017) - Platt, Laura; Powers, Laurie; Leotti, Sandra; Hughes, Rosemary B.; Robinson-Whelen, Susan; Osburn, Sherri; Ashkenazy, Elesia; Beers, Leanne; Lund, Emily M.; Nicolaidis, Christina; ,
Violence against people with developmental disabilities is a highly prevalent yet understudied phenomenon. In particular, there is a paucity of literature surrounding the role of gender and the experiences of men. Using a cross-sectional study design, we surveyed 350 people with diverse developmental disabilities about experiences of abuse, perpetrators of abuse, and their physical and mental health status. These data were analyzed to determine whether gender influenced these domains. Statistical methods included chi-square, independent t tests, logistic regression, and hierarchical multiple regressions. Male and female participants reported abuse at high rates, with 61.9% of men and 58.2% of women reporting abuse as children and 63.7% of men and 68.2% of women reporting abuse as adults. More women than men reported adult sexual abuse, but there was no gender difference in the prevalence of any other form of abuse. Women were more likely than men to identify an intimate partner as their abuser, although intimate partners represented the minority of abusers for both men and women. Violence was associated with worse health status regardless of participant gender. These findings confirm that violence is an important issue for both men and women with developmental disabilities. Although some expected gender differences arose, such as higher rates of adult sexual abuse and intimate partner violence against women, these differences were less pronounced than they are in the general population, and the overall picture of abuse was one of gender similarities rather than differences.